PELESTARIAN FAUNA DALAM UPACARA TUMPEK KANDANG SEBAGAI MEDIA PENDIDIKAN BAGI MASYARAKAT HINDU DI BALI - I Wayan Janur Divayana,S.Pd Janur (Jurnal Pendidikan Agama, 2023)
The island of Bali is imbued with Hinduism, making the existing culture very unique. Values ​​in the teachings of Hinduism are a source of existing cultural values, so that Balinese culture is religious. The holy holidays of Hinduism in Bali contain a deep meaning for the life of the Hindu community in Bali. One of these holy days is the Tumpek Kandang holy day. The issues discussed include Efforts to Harmonize Nature through Fauna Preservation and the Role of the Tumpek Kandang Ceremony as a Media for Hindu Education. This type of research is a qualitative research with library methods. After the data is collected, it will be analyzed by reducing, presenting, and drawing conclusions or verifying. The results of this study include, (1) Preserving animals through the Tumpek Kandang Ceremony has a good impact on the harmony of the universe and balancing Bhuwana Agung and Bhuwana Alit (2) Through the implementation of the Tumpek Kandang holy day as well as providing education for Hindus, especially in Bali, about the greatness of God who being everywhere or being in every place (Wyapi-Wyapaka), especially the god who animates animals with the title Sang Hyang Rare Anggon.